Aprovechamiento de Nopal Nopal Energy Bar - Sacatoro Días, Freddy Germán (2017)
The objective of this work was to formulate an energy bar with cactus pulp as a different alternative to take advantage of available resources and encourage consuming this type of product. The cactus was used fresh, through an appropriate procedure, pulp was obtained and a heat treatment was given at different concentration times and temperatures, in order to determine the physical changes such as degrees° Bx, pH and viscosity. The concentrated pulp was incorporated with a suitable proportion of oats, dehydrated uvilla, pumpkin seeds, and using honey as the sweetener. The sensory analysis of the product showed that there is a significant difference in the acceptance of the evaluated product by organoleptic characteristics as: smell, taste, color, texture and acceptability, in this case the bar made with cactus pulp, concentrated to a time of 10 minutes and at a temperature of 60 ° C, corresponding to the treatment t3 (a2b1) which presents better characteristics. Using nutritional analyzes for the best treatment, the energy bar with cactus pulp presents an energy contribution of 1173 KJ (280 cal) for a portion of 77 g, the content of fat, sodium, carbohydrates, dietary fiber and protein is 11% , 2%, 16%, 4% and 14% respectively, so its consumption is a viable alternative for taking advantage of its benefits.The parameters of physical-chemical analysis of moisture, ash, is 15.91 ± 0.08 % and 1.58%, finally the microbiological parameters of total coliforms, yeast and mold count evaluated have values within the established ranges < 10 according to the NORMA TÉCNICA INEN 1529-7.